Mycophenolate mofetil in pediatric renal transplantation without induction therapy: results after 12 months of treatment - Staskewitz, Astrid; Kirste, Günter; Tönshoff, Burkhard; Weber, Lutz T.; Böswald, Michael; Burghard, Rainer; Helmchen, Udo; Brandis, Matthias; Zimmerhackl, Lothar B. (Transplantation, 2001)
Acute rejection episodes (ARE) of kidney transplants are considered as risk factor in the development of chronic rejection. In adult renal transplantation (RTx), ARE have been significantly reduced by mycophenolate mofetil (MMF) in combination with cyclosporin (CyA) and steroids (Pred). Reports of pediatric RTx on a maintenance immuno-suppression with MMF are restricted to patients (P) after antibody induction therapy.
Gesehen am 26.01.2021